PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MACROMEDIA FLASH 8 PADA MATA PELAJARAN SIMULASI KOMUNIKASI DIGITAL - Yanti, Fitri; Fauziah, Fauziah; Ridoh, Ahmad; Tris Susanti, Desi (Information Technology Education Department, 2024)
Based on field observations, classroom learning was conducted using a blackboard and simple PowerPoint. From there, researchers came up with the idea to develop learning media using Macromedia Flash 8 to overcome students' boredom and boredom in learning. The type of research conducted is Research and Development (R&D) with the ADDIE development model, consisting of stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. However, this research only reached the implementation stage, so the evaluation was conducted as part of the implementation activities. This development research has passed several tests, namely: (1) Validity test, with results of 0.86 (software engineering aspects), 0.79 (visual communication aspects), and 0.88 (learning aspects) with valid categories. (2) Practicality test, based on teacher and student responses with a percentage value of 92.59% and 96.02% respectively, with a practical category. (3) Effectiveness test, classical test results reached 85% above the KKM, and paired t test data analysis showed an increase between pretest and post-test of 2.299. Based on the test results, it can be concluded that Macromedia Flash 8 learning media is valid, practical, and effective, and can be used to improve student learning outcomes.